Design and Evaluation of Modified Laval Nozzle for Atomization Performance - Shanshan, Tang (Universiti Malaysia Sarawak, 2025)
Particulate matter generated during the mining, processing, and transportation of coal and stone materials has become one of the primary sources of air pollution, especially fine particles with small particle sizes. The traditional nozzle requires high-pressure conditions, and the atomization droplets are large and uneven. This study aims to design a nozzle with a simple structure and good atomization performance and to study the influence of nozzle structure parameters and operating conditions on atomization performance. First, a linear Laval nozzle was designed. Then, the VOF (Volume of Fluid) model and DPM (Discrete Phase Model) of Fluent are used to simulate the internal and external fields of the nozzle and analyze the velocity, pressure, droplet size, and atomization angle. Finally, the droplet size and angle of the Laval nozzle spray were measured by experiments, and comparisons with numerical analysis were also conducted. The results show that the flow inside the linear Laval nozzle can reach supersonic speed. The optimized water pressure parameters are 0.1 MPa, air pressure of 0.5 MPa, nozzle outlet diameter of 2.5 mm, and oscillator distance of 4 mm. Compared to traditional nozzles, the water pressure is reduced by over 90%, and the D (3,2) droplet diameter decreases by over 50%. Moreover, the spray angle increases by approximately 67.5%. Some fitted curves have been plotted, enabling the prediction of velocity and atomization angle within a specific range. The linear Laval nozzle studied in this research is easy to manufacture, exhibits excellent atomization performance, operates at low pressure, and is cost-effective. Particularly, a combination-type nozzle is proposed, which expands the atomization angle. The linear nozzles are applicable in diverse enclosed environments such as mines, construction sites, and processing plants. They can improve dust removal efficiency effectively, thus significantly contributing to human health and environmental protection.